Uma história do curso de especialização em ensino de ciências naturais e matemática (EECNM) do IFRN - Campus Macau na perspectiva do ensino de matemática - Araújo, Kaline Martins (2023)
This research presents the contributions and possible limitations of the Specialization course in Teaching Natural Sciences and Mathematics (EECNM), at the Federal Institute of Science and Technology Education of Rio Grande do Norte (IFRN) – Campus Macau – Rio Grande do Norte (RN), from the perspective of teaching Mathematics. It is centered on the study of the History of the Present Time (HTP), theoretically based on the works of Dosse (2017), Lohn and Campos (2017), Cavalcanti (2019) among other authors. Supported by Valente (2017) and Garnica and Souza (2012), who study the History of Mathematics Education (HEM), it is justified by the contribution to the continuing education of Mathematics teachers and, mainly, to the teaching of this discipline in the city of Macau/ RN and region. Thus, it asks: what were the contributions and/or limitations (if any) that the EECNM provided to the continuing education of Mathematics teachers and to the teaching of Mathematics? It aims, therefore, to investigate the contributions and/or limitations of the Specialization in Teaching Natural Sciences and Mathematics from the perspective of teaching Mathematics. In this investigative field, it makes use of written sources - academic documents of students found at IFRN and the Pedagogical Project of the Course (PPC) of EECNM -, in addition to oral sources - narratives of memories of graduates, professors of the institution and also of Mathematics in the region - collected through semi-structured interviews. To do so, it resorts to the assumptions of authors who discuss qualitative research such as Stake (2011), Bogdan and Biklen (1994), Gil (2008) and (2010) and Cellard (2008), combining different methodological procedures for data analysis, with the intention of obtaining some results. At the end of this investigation, it is observed that the EECNM contributes positively to the didactic practice and academic career of graduates, even providing knowledge inherent to their intrapersonal development. It also contributes to the development of scientific production in the teaching of Mathematics in the city of Macau and region. With regard to limitations, this research pointed to the aspect of course regulation, as the curricular order in which the disciplines are offered and the rules for selecting specialization students create obstacles in the selection process. Another limiting factor observed was the low demand for this specialization in the last selection notices. Therefore, this work comprises an important record of the contributions and limitations of the EECNM of the IFRN, Macau campus, with emphasis on the teaching of Mathematics, in the city of Macau and region, from its implementation to the present day. (Year 2023).